Au-delà des bois : Une analyse des conflits socio-politiques autour de la libéralisation de la chasse en Belgique (1894-1936) - Marie Chaidron (Amnis)
This contribution aims to understand the social and political conflicts related to hunting rights in Belgium between 1894 and 1936, a period marked by socio-economic and political upheavals. At the end of the 19th century, hunting legislation has been the source of significant societal tensions, and the desire to liberalize hunting has become one of the major arguments of the Belgian Workers’ Party. The analysis goes beyond parliamentary debates to delve into rural areas, revealing the direct involvement of local actors: hunters, gamekeepers, and landowners. The term "poaching dramas" thus became a recurring subject in the judicial sections of the press from the last quarter of the 19th century onwards to describe the sometimes deadly confrontations between supporters and opponents of hunting liberalization. These conflicts reveal much deeper issues than the simple question of hunting, touching on power relations, access to resources, and divergent visions of rural life. They challenge the idea of a passive peasantry, highlighting instead the capacity for action and protest among rural populations in the face of perceived injustices.